STRATEGIC FOUNDATIONS FOR THE IMPLEMENTATION OF THE CONCEPT OF PUBLIC SAFETY IN THE INFORMATION SOCIETY (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of ensuring public safety in an information society, the strategic foundations of implementing the concept of public safety in an information society, and the prospects for implementing the concept of public safety in the new Uzbekistan. The article also analyzes the strategic foundations of implementing the concept of public safety in an information society.